Matriz de competências em ortopedia e traumatologia para a graduação médica - Siqueira, Eduardo Martins de (2022)
Introduction: The discrepancy between occurrences related to the musculoskeletal system (MSK system) and the lack of training during medical course to conduct them is clearly identified in the literature. It is estimated that about 25% of medical appointments in primary care are related to MSK system. Therefore, it is important to consider that the medical curriculum offers medical graduates the opportunity to acquire the most relevant orthopedic competences for general practitioners during graduation. Objective: Elaborate a consensus on medical competences in orthopedics and traumatology that can be used as a reference to Brazilian Medical Courses. Method: To obtain consensus, E-Delphi methodology was used. 30 doctors were invited, 10 of each of the following specialties: family practice, orthopedics and trauma. At the end, 26 doctors took part in all 3 rounds necessary to obtain the consensus. The first proposal had 41 items, product of bibliographical review and epidemiologic relevance. It was made available to the panelists through Google Forms and sent through WhatsApp. The consensus was obtained when 75% agreement was reached under the items presented. Four levels of knowledge depth were also considered when items were presented: prerequisite and essential competence, to be developed in the prescribed curriculum; and desirable and advanced competences, to be made available if there is time/opportunity to learn or through an optional. Results: A matrix of 34 competences related to the MSK system regarding all life span cycle was obtained. Conclusion: A competency matrix in Orthopedics and Traumatology was built, being 4 prerequisite, 15 essential, 7 desirable and 8 advanced, for application according to the profile of the medical curriculum. Future studies should be conducted to assess the applicability of the proposed matrix and its effectiveness.